Pendapatan Daerah Sektor Pariwisata Di KabupatenSragen Dan Faktor-Faktor Yang Mempengaruhinya - Nanditya, Desintha; , Muhammad Arif, SE.,M.Ec.Dev (2017)
The tourism sector is the sector that plays an important role especially in the formation of regional economic growth, this research aims to analyze the factors that affect the income of the region's tourism sector Sragen district, based on the literature and previous research note that a variable number of tourists per capita income, and the distance from the town center is the factors that affect the income of the region's tourism sector. The data used in this research is secondary data drawn from studies of good literature library of the Central Bureau of statistics (BPS), journals and research. Analysis tools in this research is the regression data panel by selecting the best model is the Fixed Effect Model (FEM). The results showed that a variable number of tourists per capita income, and mileage from the center of influential regional income significantly to the tourism sector in the Sragen district in 2011-2015 on the significance level of 0.05.